Advancing pharmaceutical processes and tools for improved health outcomes - Gasmelseid, Tagelsir Mohamed, 1967- (Advances in medical technologies and clinical practice book series., 2016)
"This book presents research-based perspectives on the pharmaceutical industry in today's digitally-fueled world, focusing on technological innovations for pharmaceutical applications as well as a current trends in the industry"--